CURRENT TARGET OF ANTIHYPERTENSIVE THERAPY. DATA FROM CLINICAL TRIALS. PART 2 - V. V. Popov; N. A. Bulanov; G. G. Ivanov (Рациональная фармакотерапия в кардиологии)
Arterial hypertension (HT) takes leading position in the structure of morbidity and mortality among the cardiovascular diseases in the economically developed and developing countries of the world. Despite progress in treatment of this disease, a number of people with uncontrolled or resistant HT increases. There is a problem of inefficiency of therapy or lack of patients' adherence to treatment. Therefore, search for new approaches to treatment of HT continues. Current most effective agents for blood pressure control, and possible future antihypertensive agents, are related to groups of agents, which inhibit renin–angiotensin–aldosterone system (RAAS). Novel targets for antihypertensive therapy could include the angiotensin II type 2 and type 1 receptor , neutral endopeptidase, aldosterone synthase, renalase, endothelin receptors, (pro)renin receptors, vaccine against RAAS components. Development of novel agents and approaches to HT therapy is discussed.